Review: Perbandingan Validasi dan Kadar Amlodipin dalam Sampel Plasma Darah pada Kromatografi Cair Kinerja Tinggi dan Kromatografi Cair Spektrometri Massa - Deborah Chennia Lau; Tiara Cinta Amelia; Diara Ravika Hadjami (Journal of Pharmaceutical and Sciences, 2023)
Amlodipine has a high bioavailability, a large volume of distribution, and a sufficiently long elimination half-life of 35 to 50 hours so that low plasma concentrations of amlodipine are achieved after oral administration. One of the methods used to quantify amlodipine levels is High-Performance Liquid Chromatography and Liquid Chromatography Mass Spectrometry. This review aims to compare the validation of the two methods according to the parameters and determine the advantages and disadvantages of each process in terms of accuracy in identifying samples of amlodipine in blood plasma. An article review was conducted by collecting data from 2013 to 2023 using the Google Scholar and ScienceDirect databases filtered according to the inclusion and exclusion criteria. Seven journals could be compared according to the parameters of precision, accuracy, linearity, limit of detection and quantification. Better precision and accuracy are in the High-Performance Liquid Chromatography method, and good linearity is in the Mass Spectrometry Liquid Chromatography method. Liquid Chromatography Method Mass Spectrometry is easier to detect amlodipine levels because it can detect concentrations of more minor sample levels.